ASSESSMENT OF THE QUALITY OF LIFE OF CHILDREN WITH CHRONIC KIDNEY DISEASE IS IMPORTANT INFORMATION IN PROVIDING SERVICES: SYSTEMATIC REVIEW - Purnamawati, IGA Dewi; HASSAN, HAFIZAH CHE HASSAN; SANSUWITO, TUKIMIN BIN SANSUWITO (Holistic Nursing Plus, 2023)
ABSTRACT Background: Children with chronic kidney disease (CKD) continue to face significant health challenges, with a growing morbidity rate that lowers their quality of life (QoL). Children with CKD experience complex problems physically, emotionally, socially and at school, requiring different problem solving for each child. At the assessment stage, assessing the quality of life is very important, the results of which determine the next steps regarding the child's care and treatment. Purpose: The aim of this research is to determine the best service delivery based on assessing the quality of life of CKD children based on research results. Methods: Systematic review study was for children determine the best service delivery based on assessing the QoL with CKD. Electronic database and reference list of relevant articles from 2016 to 2023. Guided by PRISMA guidelines, five electronic database PubMed, EBSCO, PROQUEST, Science Direct, and Google Scholar-were searched for relevant articles published in Indonesia and English. Results: From 11 studies, it was found that the majority of children with CKD had a low quality of life in terms of physical, emotional, social and academic function, even though the quality of life of children who underwent a renal transplant (RT) was better than children who underwent a RT, undergoing hemodialysis (HD) and peritoneal dialysis (PD), to improve the QoL proper care is needed, one of which is camping activities by camping, children assess their quality of life positively, with self-esteem as the most felt dimension. Short stature, low family income, use of dialysis, and depression are risk factors associated with lower overall QoL. Conclusion: Research reveals that almost all children with CKD score poorly on QoL assessments. Children with CKD experience a poor quality of life, and require team and comprehensive work to improve the child's quality of life. Quality of life assessment is a reflection of the need for appropriate care and treatment for the child and family. Keywords: Quality of life, Children, Chronic kidney disease